Statues - Itō, Junji, 1963- (Junji Ito story collection., 2026)
Art teacher Okabe creates strange, headless statues. One day, he is found murdered, his corpse headless. From that day on, art club member Shimada seems off somehow... Elsewhere, in a curious town custom, the dead are placed on a tatami mat and set out on the river. Kanako's grandmother lives alone in a house near this river. What did she witness at one of these funerals long ago? And a mysterious disease makes girls suddenly become more beautiful. But soon they all die. The only way to survive might be worse than death itself...Ten tales from horror master Junji Ito that will plant the seed of terror in your heart.